Pembelajaran Sosial Emosional dalam Kurikulum Indonesia - Elvinasafira, Elvinasafira (Jurnal Pendidikan Tuntas, 2025)
Social Emotional Learning (ESL) is a strategic approach in education that aims to shape students who are not only academically intelligent, but also socially and emotionally mature. This literature review aims to examine the concept, position, implementation, challenges, and strategies for strengthening ESL in the context of the Indonesian curriculum, especially the 2013 Curriculum and the Independent Curriculum. The results of the study indicate that social emotional values have been integrated into the curriculum documents, especially through strengthening the Pancasila Student Profile. However, implementation in the field still faces challenges such as limited teacher training, policy discontinuity, and disparities between regions. Therefore, an integrative strategy in thematic learning, ongoing teacher training, and cross-sector collaboration are the keys to strengthening ESL in the Indonesian education system. This study provides important implications both theoretically and practically in the development of the national curriculum and character education.